Welfare assessment: correlations and integration between a Qualitative Behavioural Assessment and a clinical/ health protocol applied in veal calves farms - Cornelis G. Van Reenen; Giulio Cozzi; Elena Tessitore; Marta Brscic; Francoise Wemelsfelder; Flaviana Gottardo (Italian Journal of Animal Science, 2010)
This study is aimed at finding correlations and possible integration among Qualitative Behavioural Assessment (QBA) and a specific protocol of clinical/health evaluation. Both welfare assessment methods were based on direct animal observation and were applied in 24 Italian veal calves farms at 3 weeks (wks) of rearing. Principal component analysis (PCA) summarized 20 QBA descriptors on two main components (PC1 and PC2) with eigenvalues above 4 and explaining 29.6 and 20.3% of the variation respectively. PCA on residuals obtained after correcting for housing condition yielded highly similar results, indicating that the rearing environment of the calves was not an important determinant of the observer reliability of QBA. A relationship was found between QBA PC2 and the presence of signs of cross-sucking recorded during the clinical visit (presence PC2=1.11 vs. absence PC2=-1.55, P<0.001). There were no other relations between the quantitative clinical measures and QBA PC’s. The frequency of farmer, veterinarian, or industry technician visits to the veal unit significantly affected QBA PC1 and PC2 scores. These results suggest that the 2 methods provide complementary types of information and can each make valid a contribution to an integrated animal welfare monitoring scheme.